Konstruksi dan Validasi Protokol Skrining Virtual Berbasis Struktur dengan Kode PDB 3MQE, 3NTG, dan 3LN0 untuk Penemuan Inhibitor Siklooksigenase-2 (COX-2) - ESTI MUMPUNI; ARGUN WIDARSA; YANTI SUSILAWATI; OISAN OISAN; ARIEF NURROCHMAD; HARNO DWI PRANOWO; UMAR ANGGARA JENIE; ENADE PERDANA ISTYASTONO (Fakultas Farmasi Universitas Pancasila, 2014)
Cyclooxygenase-2 (COX-2) inhibitors are high demand drugs in the market. However, available COX-2 inhibitors nowadays have many side effects. Therefore, there is still a need to develop more potent selective COX-2 inhibitors and one of the method that has been prove the effectivity and eficiency for new drugs research is in silico. Structure-based virtual screening (SBVS) protocols were developed to find COX-2 inhibitors using the Protein-Ligand ANT System (PLANTS) docking software, SPORES, BKChem and Open Babel. The directory of useful decoys (DUD) dataset for COX-2 was used to validate the protocols retrospectively; the DUD consist of 426 known COX-2 inhibitors and 13289 decoys. Based on criteria value of EF20% and EFmax used in the article from Huang et al (2006) and Yuniarti et al (2011), two validated protocol, AYO_COX2_v.1.1 and AYO_COX2_v.1.2 , showed good results